Design a Web-based Education Development Contribution Payment Application at SDIT Tahfidz Bintangku - Heri Susanto; Viaricha Sherly Syavitri; Dwi Yanto; Karyono (Komunitas Dosen Indonesia, 2023)
Improving services to facilitate the management and monitoring of billing and payment of SPP (Education Development Contribution) in educational institutions must get serious attention because the quality of educational institutions is greatly influenced by the availability of adequate payment management. The research method used in application development uses the waterfall method. The application developed is web-based using the Laravel 9 framework with a combination of design with boostrap so that it is more responsive and uses the Mysql database. The results of the developed application are able to assist the treasurer and student guardians in managing, provide convenience for students and parents in making payments online, reduce the need to queue at physical payment counters, save time and energy, make it easier for treasurers and parents to track payment history, can verify transactions that have been made and ensure that no payment transactions are left behind, make it easier for schools to manage financial recording processes and payment processing to be more organized and controlled quickly.